Dysglycemias in pregnancy: from diagnosis to treatment. Brazilian consensus statement - Negrato, Carlos Antonio; Montenegro, Renan M.; Mattar, Rosiane; Zajdenverg, Lenita; Francisco, Rossana P. V.; Pereira, Belmiro Goncalves; Sancovski, Mauro; Torloni, Maria Regina; Dib, Sergio A.; Viggiano, Celeste E.; Golbert, Airton; Moises, Elaine C. D.; et al. (Biomed Central Ltd., 2010)
There is an urgent need to find consensus on screening, diagnosing and treating all degrees of DYSGLYCEMIA that may occur during pregnancies in Brazil, considering that many cases of DYSGLYCEMIA in pregnant women are currently not diagnosed, leading to maternal and fetal complications. For this reason the Brazilian Diabetes Society (SBD) and the Brazilian Federation of Gynecology and Obstetrics Societies (FEBRASGO), got together to introduce this proposal. We present here a joint consensus regarding the standardization of clinical management for pregnant women with any degree of Dysglycemia, on the basis of current information, to improve medical assistance and to avoid related complications of Dysglycemia in pregnancy to the mother and the fetus. This consensus aims to standardize the diagnosis among general practitioners, endocrinologists and obstetricians allowing the dissemination of information in basic health units, public and private services, that are responsible for screening, diagnosing and treating disglycemic pregnant patients.